Ruptured uterus in a 36-week pregnant patient with hemorrhagic shock after blunt trauma in Korea: a case report - Sebeom Jeon; Suyoung Park; Soohyun Oh; Jayun Cho (Journal of Trauma and Injury)
Traumatic uterine rupture is uncommon but can be fatal and life-threatening for both the mother and infant. In addition to complications caused by trauma itself, such as pelvic fracture, gestational complications such as placental abruption, abortion, premature labor, rupture of membranes, maternal death, and stillbirth can occur. In particular, fetuses have been reported to have a high mortality rate in cases of traumatic uterine rupture. A 35-year-old pregnant female patient fell from the fourth floor and was admitted to our trauma center. We observed large hemoperitoneum, pelvic fractures, and spleen laceration, and the fetus was presumed to be located outside the uterus. The pregnant woman was hemodynamically unstable. Although the fetus was stillborn, angioembolization and surgical treatment were properly performed through collaboration with an interventional radiologist, obstetrician, and trauma surgeons. After two orthopedic operations, the patient was discharged after 34 days. This case report suggests the importance of a multidisciplinary approach in the treatment of pregnant trauma patients.